2018
DOI: 10.4103/0973-1482.187295
|View full text |Cite
|
Sign up to set email alerts
|

Application of bi-nanoparticle on dose enhancement effect in two different polymer gel dosimeter using spectrophotometer

Abstract: From our results, we infer that 0.5 mM is the optimal concentration in polymer gel to obtain good DEEs in the energy range of 1.25 MeV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We also performed XRD on a polished Bi surface (24-h pulse-plated) that matches that for Bi (Fig. 6 ) 26 , 27 .
Figure 6 XRD of a polished 24-h pulse-plated Bi coating.
…”
Section: Resultsmentioning
confidence: 99%
“…We also performed XRD on a polished Bi surface (24-h pulse-plated) that matches that for Bi (Fig. 6 ) 26 , 27 .
Figure 6 XRD of a polished 24-h pulse-plated Bi coating.
…”
Section: Resultsmentioning
confidence: 99%
“…It has been further shown that the formulation of table 1 does exhibit some dose rate dependence [20], although the severity of the variability is highly application dependent. Additional studies looking at alternate formulations have been conducted with the goal of improving dosimeter sensitivity, however, a more sensitive dosimeter than that described in table 1 has not, to the best of our knowledge, been reported nor widely adopted [21,22].…”
Section: -10mmmentioning
confidence: 99%
“…Various studies have analyzed the MRI response of polymer gels for possible application in radiotherapy dose mapping ( [58,63] and references therein). In particular, polymer gels have been investigated for dosimetry in conformal therapy, IMRT, IMAT, IGRT, VMAT and tomotherapy [55,70,83,88,102,, small photon fields [136][137][138], stereotactic radiosurgery [55,[139][140][141][142], 60-cobalt source [143,144], brachytherapy [55,85,92,[145][146][147][148][149], cyberknife [150], gamma-knife [151], low-energy X-rays [152,153], high-LET and proton therapy [55,154,155], boron capture neutron therapy [55,[156][157][158][159], for interface dosimetry in the presence of tissue inhomogeneities [55,160,161], for X-ray tubes [162] and for diagnostic nuclear medicine [163]. Recently, polyacrilamide gels were proposed for dosimetry and end-to-end test for MRI-linac apparatus [164]…”
Section: Characterization and Performancementioning
confidence: 99%
“…Various studies have analyzed the MRI response of polymer gels for possible application in radiotherapy dose mapping ([ 58 , 63 ] and references therein). In particular, polymer gels have been investigated for dosimetry in conformal therapy, IMRT, IMAT, IGRT, VMAT and tomotherapy [ 55 , 70 , 83 , 88 , 102 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ], small photon fields [ 136 , 137 , 138 ], stereotactic radiosurgery [ 55 , 139 , 140 , 141 , 142 ], 60-cobalt source [ 143 , 144 ], brachytherapy [ 55 , 85 , 92 , 145 , ...…”
Section: Polyacrylamide Gelsmentioning
confidence: 99%